Cutaneous toxicity of FDA-approved small-molecule kinase inhibitors. (2nd November 2021) - Du, Jiangxia; Yan, Hao; Xu, Zhifei; Yang, Bo; He, Qiaojun; Wang, Xiaohong; Luo, Peihua
ABSTRACT: Introduction: By 1 January 2021, the FDA has approved a total of 62 small-molecule kinase inhibitors (SMKIs). The increasing clinical use of small-molecule kinase inhibitors has led to some side effects, the most common of which is cutaneous toxicity, as reflected by approximately 90% (57 of 62) of the FDA-approved SMKIs have reported treatment-related cutaneous toxicities. Since these cutaneous toxicities may have a crucial influence on the emotional, physical and psychosocial health of the patients, it is of great importance for doctors, patients, oncologists and interrelated researchers to be aware of the cutaneous side effects of these drugs in order to make the diagnosis accurate and the treatment appropriate. Areas covered: This review aims to summarize the potential cutaneous toxicities and the frequency of occurrence of FDA-approved 62 SMKIs, and provide a succinct overview of the potential mechanisms of certain cutaneous toxicities. The literature review was performed based on PubMed database and FDA official website. Expert opinion: It is significant to determine the risk factors for SMKI-induced cutaneous toxicity. The mechanisms underlying SMKI-induced cutaneous toxicities remain unclear at present. Future research should focus on the mechanisms of SMKI-induced cutaneous toxicities to find out mechanistically driven therapies.